2017
DOI: 10.1371/journal.pone.0180304
|View full text |Cite
|
Sign up to set email alerts
|

Exodus! Large-scale displacement and social adjustments of resident Atlantic spotted dolphins (Stenella frontalis) in the Bahamas

Abstract: Over the last 20 years, significant habitat shifts have been documented in some populations of cetaceans. On Little Bahama Bank (LBB) there are sympatric communities of resident Atlantic spotted dolphins (Stenella frontalis) and bottlenose dolphins (Tursiops truncatus), monitored since 1985. The size and social structure (three clusters: Northern, Central, Southern) have been stable among the spotted dolphin community with little immigration/ emigration, even after large demographic losses (36%) following two … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
23
5

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(38 citation statements)
references
References 62 publications
(128 reference statements)
0
23
5
Order By: Relevance
“…Resident killer whale movement patterns are partially driven by density and distribution of their preferred prey species (Ford & Ellis, 2006; Heimlich‐Boran, 1986, 1988; Nichol & Shackleton, 1996). Therefore, a decline in Chinook availability at the magnitude observed may result in large‐scale spatial displacement and behavioral shifts of the SRKWs, a pattern recently reported in local populations of other marine predators including spotted dolphins ( Stenella frontalis ; Herzing et al., 2017). Among other factors (i.e., environmental contaminants and anthropogenic disturbance), declining salmon abundance is resulting in the destruction and loss of SRKW critical foraging habitat (Ford et al, 2017).…”
Section: Discussionmentioning
confidence: 57%
“…Resident killer whale movement patterns are partially driven by density and distribution of their preferred prey species (Ford & Ellis, 2006; Heimlich‐Boran, 1986, 1988; Nichol & Shackleton, 1996). Therefore, a decline in Chinook availability at the magnitude observed may result in large‐scale spatial displacement and behavioral shifts of the SRKWs, a pattern recently reported in local populations of other marine predators including spotted dolphins ( Stenella frontalis ; Herzing et al., 2017). Among other factors (i.e., environmental contaminants and anthropogenic disturbance), declining salmon abundance is resulting in the destruction and loss of SRKW critical foraging habitat (Ford et al, 2017).…”
Section: Discussionmentioning
confidence: 57%
“…This often leads to the sexes segregating, either spatially or socially (Ruckstuhl, 2007). In our review, studies have reported social segregation between the sexes in both species of bottlenose dolphins (e.g., Kent et al, 2008;Mann et al, 2012), Australian humpback dolphins (Hawkins et al, 2019;Hunt et al, 2019), Risso's dolphins (Hartman et al, 2007), Atlantic spotted dolphins (e.g., Herzing et al, 2017;Danaher-Garcia et al, 2019), and northern bottlenose whales (Gowans et al, 2001). In contrast, studies have found no evidence for sexual segregation in the association networks of killer whales (Baird and Whitehead, 2000;Williams and Lusseau, 2006;Tavares et al, 2017), pilot whales (Augusto et al, 2017), and spinner dolphins (Karczmarski et al, 2005).…”
Section: Sexual Segregationmentioning
confidence: 84%
“…The application of social network theory to conservation problems generally has the potential to improve outcomes in endangered populations (Snijders et al, 2017), and social structure has been proposed as a key determinant of population dynamics in cetaceans (Wade et al, 2012). Several studies have utilized social networks to help define management units (Alves et al, 2013;Wang et al, 2015;Esteban et al, 2016b) or to better understand populations' response to mortality and removal events (Williams and Lusseau, 2006;Herzing et al, 2017;Busson et al, 2019), however, we feel there are additional roles for social network analysis in conservation generally, and in toothed whales specifically. In many toothed whale populations, one large source of mortality is fisheries bycatch, which can simultaneously and suddenly remove entire social units.…”
Section: Future Research Directionsmentioning
confidence: 99%
“…Localized UMEs within the IRL (2001,2008,2013) are all suspected to be nonepizootic with the majority of strandings occurring in the northern IRL regions (Mosquito Lagoon, northern Indian River, and Banana River;Marine Mammal Commission 2003, 2009, 2010 which are often subjected to harmful algal blooms (Lapointe, Herren, Debortoli, & Vogel, 2015), seagrass die-offs (Kamerosky, Cho, & Morris, 2015;Lapointe, Herren, Brewton, & Alderman, 2019), and periodic fish kills (Gobler et al, 2013). Changes to primary production and prey availability due to negative environmental factors have the potential to cause drastic habitat-use shifts in cetaceans quickly (e.g., within a year; Herzing, Augliere, Elliser, Green, & Pack, 2017) or over several decades (Weinrich, Martin, Griffiths, Bove, & Schilling, 1997). Further, spatial variability in environmental conditions can affect group size (Sueur et al, 2011), cluster segregation (Busson et al, 2019;Wiszniewski, Allen, & Möller, 2009), and habitat use (Herzing et al, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…Changes to primary production and prey availability due to negative environmental factors have the potential to cause drastic habitat‐use shifts in cetaceans quickly (e.g., within a year; Herzing, Augliere, Elliser, Green, & Pack, 2017) or over several decades (Weinrich, Martin, Griffiths, Bove, & Schilling, 1997). Further, spatial variability in environmental conditions can affect group size (Sueur et al, 2011), cluster segregation (Busson et al, 2019; Wiszniewski, Allen, & Möller, 2009), and habitat use (Herzing et al, 2017).…”
Section: Discussionmentioning
confidence: 99%